Analyzes herpetofaunistic in the Park Galeno Santos Mota, São Sepé, Rio Grande do Sul, Brazil - Corrêa, Luiz Liberato Costa; Silva, Darliane Evangelho; Pazinato, Daiane Maria Melo; Fraga, Vinicius Sherer; Oliveira, Stefan Vilges de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Analyzes herpetofaunistic in urbane ways are important, because the evidence the presence that group in modified ambient can be useful for adoption of manners in ambient education and preservation of natural fragments in urbanized regions. We introduce here a preliminary list of herpetofauna found in Park Galeno Santos Mota, inserted in urbane perimeter in the municipality of São Sepé, Rio Grande do Sul.